Principles and labs for physical fitness - Hoeger, Werner W. K. (Cengage, 1997)
This fitness text contains Chapters 2-11 from Hoeger's best-selling PRINCIPLES AND LABS FOR FITNESS AND WELLNESS, with a distinct Chapters 1 and 12. This text gives students the tools to apply their learning experiences and knowledge from their fitness and wellness course using motivation techniques and behavioral modification. Perforated laboratory worksheets found at the end of each chapter make it ideal for fitness and wellness courses with a lab component.